Supramolecular Assemblies with Aggregation‐Induced Emission Properties for Sensing and Detection. Issue 8 (10th December 2021) - Dai, Dihua; Yang, Jie; Yang, Ying‐Wei
Abstract: The fabrication of new supramolecular materials for real‐time detection of analytes including ions, organic pollutants, gases, biomolecules, and drugs is of pivotal importance in industrial manufacture, clinical treatment, and environmental remediation. Incorporating fluorescent molecules with distinct aggregation‐induced emission (AIE) effects into supramolecular assemblies has received much attention over the past two decades, owing to the remarkable performance of the AIE‐active supramolecular materials in sensing and detection. In this minireview, we summarize the recent progress of superior detection systems on the basis of supramolecular assemblies accompanied with AIE features. We envision that this minireview will be helpful and timely for relevant researchers to stimulate new thinking for constructing new AIE‐based supramolecular materials with advanced architectures for effective sensing and detection. Abstract : Recent supramolecular assembly systems with aggregation‐induced emission properties for the detection of analytes including metal ions, anions, organic pollutants, gases, biomolecules, and heparin are summarized according to their unique architectures, diverse functions, outstanding sensitivity, and excellent selectivity as sensing platforms. Furthermore, the additional advantages of the marriage between supramolecular assemblies and AIE features are highlighted, and opportunities, challenges, and development perspectives of the particular combination are also discussed.